The Impact of Aging on Spatial Abilities in Deaf Users of a Sign Language. (21st November 2020) - Luna, Stéphanie; Joubert, Sven; Blondel, Marion; Cecchetto, Carlo; Gagné, Jean-Pierre
Abstract: Research involving the general population of people who use a spoken language to communicate has demonstrated that older adults experience cognitive and physical changes associated with aging. Notwithstanding the differences in the cognitive processes involved in sign and spoken languages, it is possible that aging can also affect cognitive processing in deaf signers. This research aims to explore the impact of aging on spatial abilities among sign language users. Results showed that younger signers were more accurate than older signers on all spatial tasks. Therefore, the age-related impact on spatial abilities found in the older hearing population can be generalized to the population of signers. Potential implications for sign language production and comprehension are discussed.